2016
DOI: 10.1136/jech-2015-206529
|View full text |Cite
|
Sign up to set email alerts
|

The influence of refugee status and secondary migration on preterm birth

Abstract: Refugee status, jointly with secondary migration, influences PTB among migrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 28 publications
2
33
0
2
Order By: Relevance
“…Although no previous studies have examined GDM among refugee women, previous research has examined obstetrical outcomes in general. Refugee women were at greater risk of having pregnancy complications such as preterm birth, caesarean section and low birthweight children [21,22]. By contrast, other studies have no increased risk for pregnancy complications for refugee women [23,24], and some even found, similar to our findings among women with GDM, a lower risk of preterm birth [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…Although no previous studies have examined GDM among refugee women, previous research has examined obstetrical outcomes in general. Refugee women were at greater risk of having pregnancy complications such as preterm birth, caesarean section and low birthweight children [21,22]. By contrast, other studies have no increased risk for pregnancy complications for refugee women [23,24], and some even found, similar to our findings among women with GDM, a lower risk of preterm birth [25,26].…”
Section: Discussionsupporting
confidence: 88%
“… 32 Other research suggests maternal chronic stress is an important risk factor for PTB, 33 particularly among socially disadvantaged populations. 34 Previously published research of ours found that the effect of refugee status on PTB was stronger among refugee mothers who resided in a transition country prior to arriving in Canada 7 with potentially greater exposure to psychosocial stress. The hypothesised physiological mechanism connecting psychosocial stress to both gestational diabetes and PTB involves dysfunction of regulatory hormones in the body—insulin resistance or impaired insulin metabolism leading to gestational diabetes 32 and early release of hormones required for the initiation of labour leading to PTB.…”
Section: Discussionmentioning
confidence: 79%
“…5 Department of Pediatrics, Haukeland University Hospital, Bergen, Norway. 6 Centre for Clinical Research Dalarna, Uppsala University, Uppsala, Sweden.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Migrant women may be of good health, sometimes even better health than the host population; a phenomenon often referred to as the healthy migrant effect [4,5]. However, increased risk of adverse pregnancy outcomes including preterm birth [6,7] and perinatal mortality [8] have been reported for refugees in particular.…”
Section: Introductionmentioning
confidence: 99%